STUDENTS' READING LEVEL MASTERY AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Habib, Fauji; Bahara, Susana R.; Latif, Saiful (Universitas Khairun, 2024)
This study aims to determine the level of fifth semester students in reading mastery. This research took place in the English Education Study Program, Faculty of Teacher Training and Education, Universitas Khairun Ternate. This research uses descriptive quantitative method to explain and describe the level of fifth semester students of English education study program in students' mastery of reading. Researchers collected data by giving questioners to determine students' mastery. The subjects of this study were 45 students. In this study there were no students who fell into the Excellent category. A total of 14 students (31.11%) whose test results fell into the good category. 11 students (24.44%) test results fall into the Fair category. 13 students (28.88%) test results fall into the Fair category. 7 students (15.55%) were in the Poor category. To summarize, the average score of students in mastery of English reading is still quite adequate with a total average score of 53.97. Based on this study, the researcher found that there are some difficulties of students in reading comprehension, namely on complex words or vocabulary, the ability to understand sentences.